1961
DOI: 10.1126/science.134.3487.1363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ribonuclease on Retention of Conditioned Response in Regenerated Planarians

Abstract: Conditioned planarians were transected and allowed to regenerate in a ribonuclease solution or in pond water. Heads which had regenerated in ribonuclease displayed a retention level equal to that of head and tail sections which had regenerated in pond water. However, tails regenerated in ribonuclease performed randomly although they could be retrained to criterion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…On the other hand several investigators have of fered evidences that RNA is involved in the consolidation of the memory' traces. Thus, Corning and John (1961) showed that planaria regenerated from tails of conditioned animals do not retain previous experience when regenerated in the presence of RNAase; Chamberlain el al. (1963) have shown that 8-azaguanine, a nucleic acid antimetabolite, impairs the fixation of the postural asymme try induced by cerebellar lesions; Hyden and Egyhctzi (1962) found an increased RNA concentration in central nervous neurons of rats trained on trial-and-error experiments, and Cameron el al.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand several investigators have of fered evidences that RNA is involved in the consolidation of the memory' traces. Thus, Corning and John (1961) showed that planaria regenerated from tails of conditioned animals do not retain previous experience when regenerated in the presence of RNAase; Chamberlain el al. (1963) have shown that 8-azaguanine, a nucleic acid antimetabolite, impairs the fixation of the postural asymme try induced by cerebellar lesions; Hyden and Egyhctzi (1962) found an increased RNA concentration in central nervous neurons of rats trained on trial-and-error experiments, and Cameron el al.…”
Section: Discussionmentioning
confidence: 99%
“…eliciting movement in a specific direction in a two-choice maze (Best, 1963;Corning and John, 1961;Corning, 1966;Corning, 1967;Corning et al, 1967;Humphries, 1961;McConnell, 1965;Roe, 1963) or learning to associate odorant cues (Wisenden and Millard, 2001), likewise survived regeneration of the head (Corning, 1966;Ernhart and Sherrick, 1959). The reports of persistent memory in an animal that had to regenerate its entire head (Corning, 1967) suggests approaches for investigating how information can be stored outside of the brain and imprinted on a newly regenerating brain -a truly fascinating possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 55years ago it was demonstrated that planarians could be trained to learn a task, and following amputation of the head, the animals regenerating from the original tail sections remembered the original training (Best, 1963;Corning and John, 1961;McConnell, 1965;McConnell et al, 1959). This stunning finding, suggesting that some memory may be stored outside of the head and imprinted on the new brain during regeneration, led to a myriad of subsequent associative learning studies (Cherkashin et al, 1966;Corning, 1966;Corning, 1967;McConnell, 1965;Morange, 2006;Sheiman and Tiras, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…More consistent results have been produced by attempts to interfere with the hypothesized RNA store. Corning & John (1961) reported lack of retention of a light conditioned contraction in planaria regenerated in RNAase while control groups regenerated in pond water showed a significant saving.…”
mentioning
confidence: 99%